Developmental biology: Instructions writ in blood. - Enver, T; Jacobsen, SE (2009)
It seems that growth factors may instruct blood-cell progenitors to develop into specific mature cell types, actively determining lineage choice. But is this reductionist view of cell fate overly simplistic? © 2009 Macmillan Publishers Limited. All rights reserved.